Role of pro-inflammatory cytokines in rheumatoid arthritis. - Brennan, F; Maini, R; Feldmann, M (1998)
Rheumatoid arthritis (RA) is well known to be a chronic autoimmune/inflammatory disease which leads to progressive joint damage and destruction. Less well known is the fact that in severe cases of RA, with extra-articular manifestations and multiple joint involvement, there is also a significant reduction in life expectancy [28]. Hence the need for new therapeutic agents. With the cloning of cDNAs encoding cytokines in the early to mid 1980s, it became possible to use new assays to evaluate cytokine expression in the local site of autoimmunity, the rheumatoid synovium. There were two goals. First would understanding cytokine expression help us understand the pathogenesis of RA? Secondly, would it be possible to learn enough about the cytokine network to establish possible therapeutic targets? While a complete understanding of either of these questions remains elusive, here we review the state of knowledge in early 1998, which shows that much progress has been made and that these goals have been partly reached. The clinical benefits of this knowledge are documented elsewhere in this compilation, as is the role of chemokines, anti-inflammatory cytokines and the cytokines involved in neovascularisation.